2018
DOI: 10.1039/c7ta09672k
|View full text |Cite
|
Sign up to set email alerts
|

Photoelectrochemical reduction of CO2to HCOOH on silicon photocathodes with reduced SnO2porous nanowire catalysts

Abstract: High-quality Si photoelectrodes with novel Sn nanowire catalysts convert solar energy to reduce CO2 to formic acid with high selectivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(41 citation statements)
references
References 42 publications
1
40
0
Order By: Relevance
“…[18] Numerous experimental studies have focused on the selective CO 2 electroreduction to formic acid using tin dioxide nanoparticles. [19][20][21] Meyer and co-workers investigated this topic by controlling nanoparticle size and observed that a high current density of > 10 mA cm À 2 , corresponding to formate production, can be achieved at a lower overpotential of 340 meV. [22] In another study, Kumar et al discussed the activity of reduced SnO 2 nanowires towards the selectivity for HCOOH.…”
Section: Introductionmentioning
confidence: 99%
“…[18] Numerous experimental studies have focused on the selective CO 2 electroreduction to formic acid using tin dioxide nanoparticles. [19][20][21] Meyer and co-workers investigated this topic by controlling nanoparticle size and observed that a high current density of > 10 mA cm À 2 , corresponding to formate production, can be achieved at a lower overpotential of 340 meV. [22] In another study, Kumar et al discussed the activity of reduced SnO 2 nanowires towards the selectivity for HCOOH.…”
Section: Introductionmentioning
confidence: 99%
“…The Faradaic efficiency of direct CO 2 reduction at p‐Si was shown to be high when carried out in non‐aqueous electrolytes or at high pressure . To further improve the CO 2 reduction efficiency, cocatalysts such as reduced graphene oxide, Sn nanorods, silver nanowires, and gold mesh have been combined with the semiconductor. For Ag‐catalyzed CO 2 reduction, CO is regarded as a key target compound because of its favorable economics as a building block of chemicals and fuels .…”
Section: Introductionmentioning
confidence: 99%
“…It is worth recognizing that higher photocurrent and lower onset potential values have generally been linked to catalytically-active materials which can overcome the high kinetic overpotential of the CO 2 reduction half-reaction, and by a lesser degree, the optical and charge transport properties of the photoelectrode. Single-junction expensive PV-grade materials such as Si (Fung et al, 2020;Hu et al, 2018;Rao et al, 2018), GaN (DuChene et al, 2018;Sekimoto et al, 2016), InP (Kaneco et al, 2006a;Kaneco et al, 2006b;Qiu et al, 2015;Zeng et al, 2015) and ZnTe (Jang et al, 2014;Jang et al, 2015) with excellent optical and charge transport properties have been extensively studied. Nevertheless, these materials possess poor catalytic sites for CO 2 reduction, which usually offer little to no redeeming improvements in the PEC activity as compared to those of more catalytically-active copper-based (Ghadimkhani et al, 2013;Won et al, 2014;de Brito et al, 2015;Kang et al, 2015;Kang and Park, 2017;Lee et al, 2018) or molecular metal-complex (Arai et al, 2011;Jeon et al, 2014;Huang et al, 2016;Kumagai et al, 2017) systems, whose activities have hitherto remained unparalleled.…”
Section: Pec Co 2 Reductionmentioning
confidence: 99%